a The Effectiveness of Interprofessional Simulation Training in Enhancing Emergency Response to Catastrophic Diseases: The Effectiveness of Interprofessional Simulation Training in Enhancing Emergency Response to Catastrophic Diseases - Lwy, Patrice (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
The Effectiveness of Interprofessional Simulation Training in Enhancing Emergency Response to Catastrophic Diseases